Suppliers selection in a public institution: A sustainable and hierarchical approach - Castillo Salazar, Regner Nicolás (Revista Venezolana de Gerencia, 2023)
This research analyzes the procurement supply chain management of a Peruvian public institution, using the AHP approach and sustainable supplier selection criteria. The sample included 7,833 employees of the purchasing department, including managers, administrators, assistants and collaborators. The analysis revealed 5 subgroups, the largest representing 28.04% and standing out for its emphasis on the environmental factor with an average of 62.85%. The subfactors of economic sustainability, product useful life and maintenance cost did not show significant differences in weighting, with a high average impact, 11.69% and 11.76% respectively. Therefore, companies seeking to supply these municipalities must focus on offering solutions with low maintenance costs and long useful lives to ensure economic sustainability. These results support the effectiveness of the AHP method in identifying critical factors in decision making.